Unraveling the Molecular Mechanisms Underlying Complement Dysregulation by Nephritic Factors in C3G and IC-MPGN - Donadelli, Roberta; Pulieri, Patrizia; Piras, Rossella; Iatropoulos, Paraskevas; Valoti, Elisabetta; Benigni, Ariela; Remuzzi, Giuseppe; Noris, Marina (Frontiers in Immunology, 2018)
Membranoproliferative glomerulonephritis (MPGN) was recently classified as C3 glomerulopathies (C3G), and immune-complex (IC) mediated MPGN. Dysregulation of the complement alternative pathway, driven by acquired and/or genetic defects, plays a pathogenetic role in C3G. However, alternative pathway abnormalities were also found in IC-MPGN. The most common acquired drivers are the C3 nephritic factors (C3NeFs), heterogeneous autoantibodies that stabilize the C3 convertase, C3bBb. C3NeFs are traditionally detected by hemolytic assays based on sheep erythrocyte lysis, which however do not provide a direct molecular estimation of C3bBb formation and decay. We set up a microplate/western blot assay that specifically detects and quantifies C3bBb, and its precursor, the C3 proconvertase C3bB, to investigate the complex mechanistic effects of C3NeFs from patients with primary IC-MPGN (n=13) and C3G (n=13). In the absence of properdin, 9/26 patients had C3NeF IgGs stabilizing C3bBb against spontaneous and FH-accelerated decay. In the presence of properdin the IgGs of all but one patient had C3bBb-stabilizing activity. Properdin-independent C3NeFs were identified mostly in DDD patients, while properdin-dependent C3NeFs associated with either C3GN or IC-MPGN and with higher incidence of nephrotic syndrome. When we grouped patients based on our recent cluster analysis, patients in cluster 3, with highly electron-dense intramembranous deposits, low C3 and mostly normal sC5b-9 levels, had a higher prevalence of properdin-independent C3NeFs than patients in clusters 1 and 2. Conversely, about 70% of cluster 1 and 2 patients, with subendothelial, subepithelial and mesangial deposits, low C3 levels and high sC5b-9 levels, had properdin-dependent C3NeFs. The flexibility of the assay allowed us to get deep insights into C3NeF mechanisms of action, showing that: 1) most C3NeFs bind strongly and irreversibly to C3 convertase; 2) C3NeFs and FH recognize different epitopes in C3 convertase; 3) C3NeFs bind rapidly to C3 convertase and antagonize the decay accelerating activity of FH on newly formed complexes; 4) C3NeFs do not affect formation and stability of the C3 proconvertase. Thus, our study provides a molecular approach to detecting and characterizing C3NeFs. The results highlight different mechanisms of complement dysregulation resulting in different complement profiles and patterns of glomerular injury, and this may have therapeutic implications.